Primary diffuse large B cell lymphoma of Uterine Cervix: Treatment outcomes of a rare entity with literature review. Issue 5 (6th August 2020) - Goda, Jayant Sastri; Gaikwad, Utpal; Narayan, Anand; Kurkure, Durva; Yadav, Subhash; Khanna, Nehal; Jain, Hasmukh; Bagal, Bhausaheb; Epari, Sridhar; Singh, Priya; Sengar, Manju; Laskar, Siddharth
Abstract: Background: Primary lymphomas involving the female genital tract are rare, and those arising from cervix are extremely uncommon. They are often misdiagnosed because of their rarity. Methods and cases: The treatment and clinical outcomes of the four cases treated at our institution were compared with the previously published studies. Written informed consent was taken. We highlight four cases of primary diffuse large B‐cell lymphoma of cervix treated at our institution with immunochemotherapy and radiotherapy. The mean age was 50 years (range, 39‐62 years). Three patients had stage I disease while one had stage II disease. All the patients were in complete remission following treatment with immunochemotherapy and radiation therapy. The average disease free survival was 20 months (range, 8‐43 months). None of the patients had any local or systemic relapse. Conclusion: These cases highlight the physicians to be aware of this entity as their management, natural history and prognosis is completely different from squamous carcinomas of the cervix. Surgery should not be attempted in these patients. Immunochemotherapy and radiotherapy results in favorable clinical outcomes.